Culture, Religiosity and Female Labor Supply - Duygu Guner; Gokce Uysal (Institute for the Study of Labor (IZA), 2014)
Does culture affect female labor supply? In this paper, we address this question using a recent approach to measuring the effects of culture on economic outcomes, i.e. the epidemiological approach. We focus on migrants, who come from different cultures, but who share a common economic and institutional set-up today. Controlling for various individual characteristics including parental human capital as well as for current economic and institutional setup, we find that female employment rates in 1970 in a female migrant's province of origin affects her labor supply behavior in 2008. We also show that it is the female employment rates and not male in the province of origin in 1970 that affects the current labor supply behavior. We also extend the epidemiological approach to analyze the effects of religion on female labor supply. More specifically, we use a proxy of parental religiosity, i.e. share of party votes in 1973 elections in Turkey to study female labor supply in 2008. Our findings indicate that female migrants from provinces that had larger (smaller) shares of the religious party votes in 1973 are less (more) likely to participate in the labor market in 2008. An extended model where both cultural and religiosity proxies are included shows that culture and religiosity have separately significant effects on female labor supply behavior.
Keywords: J16; J21; Z10; 330; culture; female labor force participation; gender